Wykonaj działania
a) a+(a-b)=
b) 2x-(x+4)=
c) 7-(-x+6)=
d) -(x+4)+(x-5)=
e) 1-(t+p)-(t-2)=
f) -(-y+2)+(-2y-4)=

Zapisz w jak najprostszej postaci :
a) (a+b) - (2a-b) - (a-2b)=
b) (3x-y+1) - (x+y)+(y-x)=
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)=
d) (2ab+a+3)-(3ab-a+3)=
e) (4x² - 3x) - (x+0,1x²)-(x²- 0,1x)=

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-04T17:04:21+01:00
Wykonaj działania

a) a+(a-b)=a+a-b
b) 2x-(x+4)=2x-x+4=x+4
c) 7-(-x+6)=7+x+6=13+x
d) -(x+4)+(x-5)=-x+4+x-5=2x+9
e) 1-(t+p)-(t-2)=1-t+p-t-2=-1-2t+p
f) -(-y+2)+(-2y-4)=y+2-2y-4=-y-2

Zapisz w jak najprostszej postaci :
a) (a+b) - (2a-b) - (a-2b)=a+b-2a-b-a-2b=-2a-2b
b) (3x-y+1) - (x+y)+(y-x)=3x-y+1-x+y+y-x=x+y+1
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)=-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
d) (2ab+a+3)-(3ab-a+3)=2ab+a+3-3ab-a+3=-ab+6
e) (4x² - 3x) - (x+0,1x²)-(x²- 0,1x)=4x²-3x-x-0,1x²-x²+0,1x=2,9x²2,1x